The role of aqueous Ocimum Basilicum extract for monitoring the corrosion inhibition of carbon steel used in sanitation plants and its effect on Escherichia coli - El Aziz Fouda S. Abd; Khateeb Ayman Y. El; Zhery Hesham H. El; Mohamed Fakih (Zaštita Materijala, 2016)
The inhibitive effect of aqueous plant extract of Ocimum Basilicum was tested as green corrosion extract for CS(CS) in 3.5% NaCl and 16 ppm Na2S. It has excellent inhibition efficiency (% P) of about 88% provided by weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), and electrochemical frequency modulation (EFM) measurements. The increase of the extract concentration leads to increase in the % P. The adsorption of the extract on the CS surface obeys Langmuir adsorption isotherm with physical adsorption on the metal surface. The analysis of EDX and SEM confirmed the formation of the extract precipitates on the metal surface, reducing the corrosion reaction. The biological test of the extract on Escherichia Coli culture shows that there no effect on the biological activity of Escherichia Coli and can be applied safely without any harmful effect on sanitation plants.